Implications of Climatic Stressors on Agro-Pastoral Resources Among Mbororo Communities Along the Slopes of Kilum-Ijim Mountain, North West Region, Cameroon - Kongnso, Moye Eric; Buba, Umaru Hassan; Nfor, Julius Tata (Frontiers in Sustainable Food Systems, 2021)
Mountains are rich in pastures and water for agro-pastoral resources and supports rain-fed farming that sustain the livelihoods of many indigenous communities. This work seeks to examine the implications of climatic variability on agro-pastoral resources (pasture land, water) and food security within the Mbororo communities. To ascertain this, 350 household questionnaires were randomly administered in 4 Mbororo Ardorates and in-depth interviews conducted with local authorities. Quantitative and qualitative analysis of data collected revealed that the link between climate, land and water is paramount in animal rearing and crop farming in mountains. Cattle rearing and crop farming has been the main source of livelihoods for about 90% of the Mbororos as they depend on it for food and income. Cattle rearing systems are semi-normadic and transhumant while crop production is rain-fed. Climatic perturbations characterized by frequent dry spells, rainfall anomalies and fluctuations in dates of onset and termination of rains have disrupted the agro-pastoral calendar, reduced pastures and shrinked water courses. The consequence has been a fall in food production and food insecurity. Surveys indicated that the production of milk which is an important source of diet has fallen by 10%. Encroachments into grazing lands by crop farmers, invasion by unproductive grass species and farmer-grazer conflicts are aggravated by climatic stressors. The Fundong council and traditional authorities of the Kom Fondom have been working together to demarcate grazing land and provide water for cattle rearing. Mbororo communities are equally diversifying their activities to ensure food availability.